Mechanism for microbial population collapse in a fluctuating resource environment. Issue 3 (20th March 2017) - Turkarslan, Serdar; Raman, Arjun V; Thompson, Anne W; Arens, Christina E; Gillespie, Mark A; von Netzer, Frederick; Hillesland, Kristina L; Stolyar, Sergey; López García de Lomana, Adrian; Reiss, David J; Gorman‐Lewis, Drew; Zane, Grant M; et al.
Abstract: Managing trade‐offs through gene regulation is believed to confer resilience to a microbial community in a fluctuating resource environment. To investigate this hypothesis, we imposed a fluctuating environment that required the sulfate‐reducer Desulfovibrio vulgaris to undergo repeated ecologically relevant shifts between retaining metabolic independence (active capacity for sulfate respiration) and becoming metabolically specialized to a mutualistic association with the hydrogen‐consuming Methanococcus maripaludis . Strikingly, the microbial community became progressively less proficient at restoring the environmentally relevant physiological state after each perturbation and most cultures collapsed within 3–7 shifts. Counterintuitively, the collapse phenomenon was prevented by a single regulatory mutation. We have characterized the mechanism for collapse by conducting RNA‐seq analysis, proteomics, microcalorimetry, and single‐cell transcriptome analysis. We demonstrate that the collapse was caused by conditional gene regulation, which drove precipitous decline in intracellular abundance of essential transcripts and proteins, imposing greater energetic burden of regulation to restore function in a fluctuating environment. Synopsis: Frequent resource fluctuation can result in the collapse of a community of a sulfate reducer and methanogen. A single regulatory mutation in the sulfate reducer can prevent collapse, demonstrating that extensive regulation can be detrimental in a highly fluctuating environment. Conditional gene regulation required for adapting to new environments can become detrimental and lead to population collapse when resource fluctuations are too frequent. The underlying mechanism for population collapse traces back to regulation‐driven dilution of essential cellular components. The energetic cost of restoring function, therefore, becomes progressively more burdensome to a point that is unsustainable. The collapse can be rescued by disruption of conditional regulation of essential transcripts and proteins. Abstract : Frequent resource fluctuation can result in the collapse of a community of a sulfate reducer and methanogen. A single regulatory mutation in the sulfate reducer can prevent collapse, demonstrating that extensive regulation can be detrimental in a highly fluctuating environment.